The distributions by sex, hand and finger of the primary classification of Brazilians’ fingerprints (Research, Society and Development, 2022)
From the primary classification, also known as fundamental type, of the 2,000 (two thousand) fingerprints of 200 (two hundred) ten-print cards (100 from men and 100 from women), we analyzed the existence of statistically significant differences, through Pearson’s chi-square test, among the distributions of the four most common fundamental types of Juan Vucetich (internal loop, external loop, whorl and arch) and sex, hand and fingers. It is not known that similar studies have been undertaken for the Brazilian population. The occurrence of the fundamental type was independent of sex, but may depend on the hand and finger. The dependence on the hand is stronger for the internal loop and external loop types than for the arch and whorl types. The arch type, when it occurs, is more frequent in the index and middle fingers, but can appear in any fingers of any hand; the whorl type, is more frequent in the ring fingers, thumbs and index fingers, but can also occur in any finger of any hand. The internal loop type is more common in the fingers of the left hand, being rare in the right hand, with the exception of the right index finger; and symmetrically, the external loop type is more common on the fingers of the right hand, rarely appearing on the left hand, with the exception of the left index finger.